Object Suffixes as Incorporated Pronouns in Seereer - Baier, Nico (My University, 2018)
In Seereer (Atlantic, Senegal), singular pronominal objects are obligatorily marked by an object suffix on the verb. This paper provides the first comprehensive description of this object suffixation pattern, a topic that has been only cursorily described in the extant literature on Seereer (cf. Renaudier 2012). In addition, I provide a preliminary theoretical account of the Seereer object suffix system. I argue that Seereer object suffixes are best analyzed as incorporated pronouns. Evidence for such an analysis comes from the following: (i) an object suffix may never occur with an in situ object DP; (ii) an object suffix may not double an extracted object in relative clauses, wh-questions, or focus constructions; (iii) there is only one object suffix allowed per clause; and (iv) an object suffix may reference either object in a double object construction. I argue that object suffixes raise to Spec-vP and are subsequently incorporated in the verb via m-merger (Matushansky 2006, Kramer 2014, Harizanov 2014). This analysis elegantly derives the behaviors listed above. Such an approach also allows us to integrate the Seereer object suffixation data into the broader understanding of cliticization patterns crosslinguistically, thereby enriching our understanding of object marking systems in verbs.
Keywords: Incorporated Pronouns; Seereer; Object Suffixes